Replicating and Extending Bourdon's (1902) Experiment on Motion Parallax. (January 2013) - Ono, Hiroshi; Lillakas, Linda; Kapoor, Anjani; Wong, Irene
Bourdon conducted the first laboratory experiment on observer-produced motion parallax as a cue to depth. In three experiments, we replicated and extended Bourdon's experiment. In experiment 1, we reproduced his finding: when the two cues, motion parallax and relative height, were combined, accuracy of depth perception was high, and when the two cues were in conflict, accuracy was lower. In experiment 2, the relative height cue was replaced with relative retinal image size. As in experiment 1, when the two cues (motion parallax and relative retinal image size) were combined, accuracy was high, but when they were in conflict, it was lower. In experiment 3, the stimuli from experiments 1 and 2 were viewed monocularly with head movement and binocularly without head movement. In the binocular conditions, accuracy, certainty, and the extent of perceived depth were higher than in the monocular condition. In the conflict conditions, accuracy, certainty, and the extent of perceived depth were lower than in the no-conflict condition, but the extent of perceived motion was larger. These results are discussed in terms of recent findings about the effectiveness of motion parallax as a cue for depth.